RELATIONSHIP BETWEEN PREFERENCES OF MATERIALS AND ACTIVITIES OF AQUATIC SWIMMING THIRD CHILDREN'S CHILDREN (Fiep Bulletin - online, 2010)
Instructional materials center can make easier the teaching of swimming depending on how they are used. The objective of this study was to identify the types of materials and swimming activities that children aged 7 to 10 years like the most. The sample consisted of 70 children. A questionnaire was developed to serve as an evaluation tool. We calculated the Fisher correlation to relate the responses of the instrument. The correlation between "materials" and "water activities" showed a high incidence of "float-shaped rug" with competitive activities and recreational activities. We conclude that the materials that bring more pleasure for use in swimming lessons are the "float-shaped rug" and "float-shaped cylinder" and the favorite activities are recreational and competitive.
Keywords: Swimming; learning materials; preferences; water activities